A Wideband and Efficient Patch Antenna with Two Different Feeding Mechanisms for Ku/K Bands Applications - Gulzar Ahmad; Muhammad Inayatullah Babar; Siddique Ali; Faheem Ali (Mehran University Research Journal of Engineering and Technology, 2020)
Low BW (Bandwidth) is a major limitation of microstrip antennas. A patch antenna having a large BW for Ku band applications is demonstrated in this manuscript. The skills of Defected Ground Structure (DGS) and defected driven patch were engaged to widen its BW. Four slices have also been confiscated from the ground for upgrading various characteristics. It is established on the basis of this study that it can be employed in spectrum defining and bands. It puts forward an impedance BW of 8GHz, which is appropriate for numerous applications. The ground/substrate of the structure under consideration is 22×10-3m long and 10×103m wide and these specifications imply that the volume of this design is very small. The entire structure’s utmost thickness is 1.67×10-3m. It can be easily installed in relevant handy electronic devices. Investigations and analysis in this case are made with computer software known as Computer Simulation Technology. The simulated design exhibits a very good gain and efficiency. Deviation in the gain of the simulated design was from 4.4 7.3dBi and it guaranteed the highest efficiency of 98.6%. Some minor changes in the antenna resulted in expansion in the BW from 8GHz to 14GHz. The return loss which was recorded at frequency of 18.15GHz went to 48.97dB and the mentioned changes assured the uppermost efficiency of 83.1%. The fabricated antenna achieved a bandwidth of 28GHz which is far better than the simulated bandwidth.